Who's fallen asleep? : ...is it the fluffy sheep? - Barker, Stephen, 1976- (London : Usborne, 2018)
Who's wearing blue socks? Who's friends with the fox? This adorable book is full of rhyming questions for little children to answer by looking at and talking about the charming illustrations. A lovely way to encourage young children to talk and form sentences, and a delightful book to enjoy together.
On board pages.
Preschool.
Keywords: Animals -- Juvenile fiction; Animals -- Juvenile fiction. -- Infancy; Stories in rhyme; Board books